A SYSTEMATIC REVIEW : PENGELOLAAN HUBUNGAN PEMASOK STRATEGIS DAN INTEGRASI RANTAI PASOK - Yunita Sari Rioni; Afifah Adillah; Iskandar Muda (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study presents a comprehensive systematic review and synthesis of contemporary research on supplier relationship management (SRM), supply chain management (SCM), and their integration toward achieving sustainable competitive advantage. Through analysis of 12 peer-reviewed articles from Emerald Publishing journals spanning 2022-2025, this research identifies key mechanisms through which SRM practices influence organizational performance outcomes. The review reveals that effective SRM operates through three critical pathways: (1) collaborative practices and integration mechanisms, (2) environmental and relational alignment, and (3) dynamic capabilities development. Findings indicate that while direct effects of SRM on performance exist, the relationship is mediated by variables such as supply chain responsiveness, procurement performance, value co-creation, and knowledge-sharing capabilities. The study proposes an integrated conceptual framework highlighting the role of moderating variables including ambidexterity, organizational capabilities, and relational governance. Implications for supply chain practitioners and policymakers are discussed, with emphasis on the need for holistic, stakeholder-aligned approaches to supplier management in increasingly complex and disrupted business environments. This synthesis contributes to theory development in SCM research and provides actionable insights for organizations seeking to enhance supply chain resilience and competitive positioning